TWELVE ESSAYS ON 20th CENTURY UKRAINIAN LITERARY STUDIES: A NEW BOOK BY IVANO-FRANKIVSK SCHOLAR STEPAN KHOROB - Rudnytzky, Leonid (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
Літературознавчі етюди: Дослідження про західноукраїнських та еміграційних учених першої половини ХХ століття (Literary Studies: Research on Western Ukrainian and Emigré Scholars of the First Half of the Twentieth Century, Ivano-Frankivsk, 2020)